Empowering Squatter Citizen : Local Government, Civil Society and Urban Poverty Reduction - Satterthwaite, David (Taylor and Francis, 2012)
With the rapid growth in urban poverty in Africa, Asia and Latin America, most cities now have 30 to 60 per cent of their population living in shanty towns. The civil and political rights of these people are either ignored or constantly contravened. They face multiple deprivations, including hunger, long hours working for inadequate incomes; illness, injury and premature deaths that arise from dangerous living conditions and inadequate water supplies, sanitation and healthcare. Many face the constant threat of eviction and other forms of violence.